Cultura tributaria y su relación con la recaudación del impuesto predial en la Municipalidad Distrital de San Juan Bautista 2024 - Alegria Trigoso, Adrian Diderot (2025)
The study aimed to determine the relational connection between tax culture and property tax collection in the District Municipality of San Juan Bautista, 2024. It was quantitatively focused and designed to avoid experimental methods, being cross-sectionally correlational, and showed that the Spearman coefficient was 0.846**, with sig=0.000**; concluding the existence of a correlational relationship between the examined variables. These findings provide an empirical basis for designing public policies aimed at strengthening citizen tax compliance, with a direct impact on the financial sustainability of local governments.